Effectiveness of Cognitive Social Counseling Technique to Improve The Nature of Sympathy Sociodramas - Andita Widyanti; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
This study Aimed to Determine the effectiveness of cognitive counseling socio-dramas social engineering to improve sympathy. The research is a quasi-experimental design with pre-test and post-test control group. The population of this study was 72 students. The samples of this study are 36 students. The counseling was held in the lesson study activity. Methods of collection of data using questionnaires sympathetic nature to help others with 30 items. The results of the analysis of data indicate there was a significant difference the sympathy between the students in cognitive socio-drama counseling than the students in the control group